2012
DOI: 10.5114/aoms.2012.29281
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research Strain of experimental animals and modulation of nitric oxide pathway: their influence on development of renal failure in an experimental model of hepatorenal syndrome

Abstract: IntroductionPathomechanism of HRS is still poorly understood. The aim of our study was: (1) to test whether different strains of rats could develop typical HRS, and (2) to estimate the influence of activation and inhibition of nitric oxide for development of renal failure in course of HRS.Material and methodsFirst, we used 16 of Wistar and 16 of Sprague-Dawley rats in galactosamine model of HRS. Next, we used 48 of SDR rats, which received saline, N-nitro-L-arginine or L-arginine before and after liver damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
2
10
0
1
Order By: Relevance
“…Anand et al [ 23 ] presented a model of acute liver and renal failure after Ga1N administration to Sprague-Dawley rats in a standard and repeated manner. The findings of our previous study [ 22 ] also showed that acute functional renal failure can occur as a result of acute liver injury and liver failure after Ga1N administration, despite the absence of any histopathological features of renal injuries. We showed there that the development and the grade of renal failure in experimental HRS models may depend on the genetics of the experimental animals [ 22 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Anand et al [ 23 ] presented a model of acute liver and renal failure after Ga1N administration to Sprague-Dawley rats in a standard and repeated manner. The findings of our previous study [ 22 ] also showed that acute functional renal failure can occur as a result of acute liver injury and liver failure after Ga1N administration, despite the absence of any histopathological features of renal injuries. We showed there that the development and the grade of renal failure in experimental HRS models may depend on the genetics of the experimental animals [ 22 ].…”
Section: Discussionmentioning
confidence: 73%
“…The kidneys are intact both in histological and electron microscopy examination and a renal tubular cell line incubated with Ga1N did not show any nephrotoxic effect [ 23 ]. Within 24–48 h of GalN administration, acute liver injury, acute liver failure, and the resultant acute functional renal failure develop in the experimental animals [ 22 ]. Liver injury and liver failure manifest by accumulation of bilirubin, aminotransferase, and ammonia and decrease in albumin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the effect of experimental d ‐GalN‐induced acute liver failure in different tissues . Consequently, very little information is available on the effects of d ‐GalN on the brain tissues of rats…”
Section: Discussionmentioning
confidence: 99%
“…Javlé et al [ 10 ] and Makin et al [ 11 ] observed a significant reduction in renal blood flow, in addition to hemodynamic changes in the splanchnic vascular bed following the administration of GAL to rats. We also found that animals rapidly developed functional acute renal failure, the development and the degree of which depended on the strain of animal tested, in addition to acute damage and liver failure, following intoxication with GAL [ 12 ]. However, the previous studies investigated the impact of other factors on the development of ALF and associated complications rather than the ALF model itself.…”
Section: Introductionmentioning
confidence: 99%